Investigating the Glass Properties when Using Electric Arc Furnace Dust As Coloring Agent - Tran, Thi Thu Hien; Nguyen, Sy Long (JST: Engineering And Technology For Sustainable Development, 2025)
Electric Arc Furnace Dust (EAFD) and wasted glass are two types of waste in industry and daily life, so they must be recycled to recover some useful elements. The production of colored glass is one of the methods used to recycle the electric arc furnace dust to take advantage of the coloring element in the dust. To use this colored glass for decoration, it is also necessary to test its durability. The present study focuses on the properties of colored glass when using electric furnace dust. The investigation examines the chemical composition and phase structure of the colored glass, containing varying dust amounts of 0.5:99.5; 2:98; 5:95; 10:90 and 15:85. Using SEM-EDX analysis and compressive strength testing, the results show that changing the percentage of electric arc furnace dust in the glass makes a difference in its compressive strength. This change in strength is due to the distribution of dust particles within the glass matrix as a reinforced frame. Detailed discussion will be presented in the text section.